THE APPOINTMENT OF THE FEMALE SYARIE JUDGES IN SYARIAH COURT IN MALAYSIA: CHALLENGES AND RECOMMENDATION (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
The appointment of female judges in Malaysia has been debated since 2016. Previously, in Malaysia, women had to overcome significant challenges of being on the bench in the Syariah court system as a national fatwa prohibited women from being appointed as judges. It took over two decades for the National Fatwa Committee to overrule its previous decision allowing women to be appointed as Syariah court judges provided that they met the qualification requirements. Thus, this paper examines the extent of a woman's eligibility to become a judge from the perspective of syariah and the Malaysian legal framework. In addition, this paper also identifies the challenges faced by female syariah court judges in Malaysia and proposes several recommendations to overcome these challenges. In this study, a qualitative methodology was employed to analyze the data through a case study and content analysis method. For the case study approach, make observations on case law related to this research topic and for content analysis, the data obtained in the form of a document or text are analyzed using content analysis. The findings indicated that there are three views on the appointment of female judges in Syariah court: total prohibition, permissible for all cases, and permissible except for Hudud and Qisas. The challenges that will be faced as a female syarie judge are complex and challenging cases, many cases, and public perception. Among the proposed recommendations are to consult with experts, establish specialized courts, and actively advocate for gender equality. This research has the potential to improve access to justice for women in Malaysia and promote more inclusive and equitable legal system.